Cyberbullying em adolescentes brasileiros - Wendt, Guilherme Welter (Universidade do Vale do Rio dos Sinos, 2012)
Cyberbullying is understood as an intentional subtype of aggressive behavior that occurs through interactive electronic media (computers, mobile phones, social network sites), held by one or more persons against other in an unequal power relationship, where the victims often can’t defend her or himself. Recent studies points that cyberbullying is a risk factor for anxiety symptoms, depression, suicide ideation, substance abuse, among other risky development situations. Therefore, little attention has been given to this phenomenon in Brazil and Latin America. In this sense, this thesis’s aim was to investigate the cyberbullying, through two different studies, a theoretical and an empirical study. The theoretical study, described in section 1, brings evidences about the phenomenon prevalence in different countries, besides discussing consequences and conceptual aspects that differ bullying from cyberbullying. As well as, risk and protection factors related to cyberbullying are treated and actual studies about this topic are deeply revised and discussed. The empirical investigation, in section 2, was held with adolescents aged from 13 to 17 years-old (N=367), from Public and Private schools from Porto Alegre area, South Brazil. The main objective was to analyze cyberbullying prevalence and its relation with depression symptoms, verifying possible differences between boys and girls and between participants’ age differences. A high percent of adolescents referred to be involved in cyberbullying (72.7% cyber aggression and 75.6% in cyber victimization), and no gender differences were found. Significant and positive associations between cyberbullying participants’ age, time spent in internet and depression were identified. Adolescents who were victims and/or aggressors in cyberbullying showed higher levels of depression compared to cyberbullying uninvolved youth. Sociodemographic data related to adolescents’ interaction with technological and virtual tools are also described and discussed. It was possible to verify that cyberbullying is extremely relevant phenomenon that still needs to be largely studied in Brazilian context. Studies point to how much this process can represent a risk factor to youth development and emphasize the importance of researches that may support interventions. Data from the empirical study confirmed evidences found in literature, as well as showed cultural differences related to this process. Also is presented, at the end of this investigation, suggestions for future studies, as well as the study limitations.
Keywords: Depression; Adolescence; Depressão; Cyberbullying; Bullying; Adolescência; ACCNPQ::Ciências Humanas::Psicologia